Asuhan Keperawatan Anak Pada Pasien Dengan Pneumonia Neonatal Diruang Perinatologi Rumah Sakit Aisyiyah Pariaman Tahun 2026 - Annisa Salsabila; Prima Yoselina; Reska Handayani; Yessy Aprihatin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Neonatal pneumonia is an acute lung infection affecting newborn infants, characterized by respiratory distress such as tachypnea, chest wall retractions, and additional breath sounds, and may be accompanied by elevated body temperature and difficulty breastfeeding. The purpose of this study was to describe pediatric nursing care for patients with neonatal pneumonia in the Perinatology Ward of Aisyiyah Pariaman Hospital in 2026. This study used a case study method with a nursing care approach, including assessment, diagnosis, intervention, implementation, and evaluation, with data collection through interviews, observation, physical examination, and documentation. The study was conducted from March 11 to March 15, 2026, with the research subject being Baby of Mrs. S, diagnosed with neonatal pneumonia and hospitalized in the Perinatology Ward of the hospital. The results of the study identified several nursing problems, namely ineffective airway clearance, ineffective breathing pattern, neonatal jaundice, and knowledge deficit. After nursing interventions were provided, including airway management, ventilation support, and phototherapy, the patient’s condition improved, as evidenced by decreased respiratory rate, disappearance of additional breath sounds, absence of retractions, reduced bilirubin levels, and increased parental knowledge. All nursing problems showed improvement and were resolved, indicating that the nursing care provided was effective in improving the patient’s condition. It is recommended that the family improve infant care, maintain environmental hygiene, and monitor the baby’s condition regularly to prevent complications. It is recommended that families, especially mothers, improve infant care, maintain environmental and vaginal hygiene, wash hands before caring for the baby, and routinely monitor the baby’s condition to prevent complications.